2017
DOI: 10.3389/fpls.2017.00532
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nitrogen Rate and Planting Density for Improving Yield, Nitrogen Use Efficiency, and Lodging Resistance in Oilseed Rape

Abstract: Yield and lodging related traits are essential for improving rapeseed production. The objective of the present study was to investigate the influence of plant density (D) and nitrogen (N) rates on morphological and physiological traits related to yield and lodging in rapeseed. We evaluated Huayouza 9 for two consecutive growing seasons (2014–2016) under three plant densities (LD, 10 plants m−2; MD, 30 plants m−2; HD, 60 plants m−2) and four N rates (0, 60, 120, and 180 kg ha−1). Experiment was laid out in spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…Seed yield per plant decreased with increasing plant density due to the fierce competition for light and nutrients among individuals [34,52]. The plant density of 40 and 30 plants m −2 was 2.0 and 1.5 times the plant density of 20 plants m −2 , respectively; however, the seed yield of 20 plants m −2 (39.5 g plant −1 ) was only 1.5 and 1.2 times the seed yield under 40 (26.0 g plant −1 ) and 30 (33.2 g plant −1 ) plants m −2 , indicating that the overall seed yield could be greater with plant density beyond 20 plants m −2 in quinoa production, comparable to the results of seed dry matter in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Seed yield per plant decreased with increasing plant density due to the fierce competition for light and nutrients among individuals [34,52]. The plant density of 40 and 30 plants m −2 was 2.0 and 1.5 times the plant density of 20 plants m −2 , respectively; however, the seed yield of 20 plants m −2 (39.5 g plant −1 ) was only 1.5 and 1.2 times the seed yield under 40 (26.0 g plant −1 ) and 30 (33.2 g plant −1 ) plants m −2 , indicating that the overall seed yield could be greater with plant density beyond 20 plants m −2 in quinoa production, comparable to the results of seed dry matter in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most of these enhanced nitrogen management techniques either optimize the total N input or decrease the N losses, they require extensive technical support that is limited by its dissemination to farmers, with the overall yield remaining unchanged. Proper management of nitrogen fertilizer usage in rice fields has been considered an effective field tactic, not only for increasing grain yield, but also for its beneficial environmental impacts.In addition to nitrogen, planting density is another key factor in determining crop yield [21,22]. Due to labor shortages and high seed costs, farmers transplant rice with a wide spacing.…”
mentioning
confidence: 99%
“…In addition to nitrogen, planting density is another key factor in determining crop yield [21,22]. Due to labor shortages and high seed costs, farmers transplant rice with a wide spacing.…”
mentioning
confidence: 99%
“…A statistical analysis of plant density data from national and regional yield trials in China showed values varying from 225,000 to 300,000 plants ha −1 from 2005 to 2012, which increased to 345,000 to 405,000 plants ha −1 from 2013 to 2014 (Hu et al, 2017). The seed yield response to plant density has been adequately described by a quadratic parabola model (Yantai et al, 2016;Khan et al, 2017). The optimum plant density of rapeseed varies with the climatic conditions, level of cultivation mechanization, and cultivar characteristics.…”
mentioning
confidence: 96%
“…A high plant density usually exacerbates plant competition for resources, with rapeseed having a moderate adjustment response to increased plant density. The seed yield response to plant density has been adequately described by a quadratic parabola model (Yantai et al, 2016;Khan et al, 2017). The seed yield response to plant density has been adequately described by a quadratic parabola model (Yantai et al, 2016;Khan et al, 2017).…”
mentioning
confidence: 99%